Effect of zingerone on high fructose diet-induced metabolic derangements in growing Sprague-Dawley rats - Lushozi, Nondumiso Immaculate (My University, 2020)
The consumption of fructose increases the risk of obesity, non-alcoholic fatty liver disease(s) (NAFLD) and metabolic syndrome in children. Zingerone, a phytochemical largely found in ginger, has antidiabetic and anti-obesogenic properties. This study investigated the potential of orally administered zingerone to protect growing Sprague-Dawley rats against dietary fructose induced metabolic derangements. Seventy-seven (38 male; 39 female) Sprague Dawley rats in an interventional study, were randomly allocated to four treatment regimens which were administered for 12 weeks. The administered treatment regimens were as follows: regimen I: standard rat chow (SR) + plain water (PW) + plain gelatine cube (PC), regimen II: SR + 20% (w/v) fructose solution (FS) + PC, regimen III: SR + FS + 100 mg/kg/day of fenofibrate in gelatine cube and regimen IV: SR+ FS + 20 mg/kg/day of zingerone in gelatine cube. Two days before euthanasia the rats’ tolerance to an oral glucose load was determined. At study termination following a 12-hour fast, but with access to drinking water, the rats’ body weights were determined. Blood was collected, blood glucose concentration measured and plasma harvested. Following dissection the empty carcass weight, tibiae length, weight, and weight to length ratio were determined. Liver and visceral fat weights were measured. Plasma AST activity as well as triglyceride, cholesterol, insulin and adiponectin concentrations were determined. HOMA-IR was calculated. The liver lipid content and histology were determined. Fructose consumption significantly increased (P < 0.05) hepatic lipid accretion and caused hepatic steatosis but did not (P>0.05) have an effect on tolerance to an oral glucose challenge, body weight, empty carcass weight, tibiae indices, circulating metabolite (glucose, triglyceride, insulin and adiponectin) concentrations. Zingerone did not prevent the increased liver lipid accretion in the high-fructose diet-fed rats, but it prevented the development of steatosis in male and female rats. Fenofibrate mitigated the fructose-induced increase in liver lipid accretion and prevented steatosis but it caused glucose and insulin-related disturbances in male rats and increased (P < 0.05) plasma triglycerides in female rats. Fenofibrate also significantly increased (P < 0.0001) liver weights in male and female rats. Zingerone may potentially be used in the prevention of fructose diet-induced hepatic steatosis but the mechanism(s) of it potential beneficial effects require further interrogation.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Medicine to the Faculty of Health Sciences, School of Physiology, University of the Witwatersrand, Johannesburg, 2020